On the application of two small parameters method - Astrauskienė, E.; Ragulskis, Liutauras; Tiknevičienė, Irena (Lietuvos matematikos rinkinys, 1997)
The carried body in the analysed vibrating system iš excited by disbalanced vibrators with asynchronous engines. The analysis of multiple dynamic synchronization by an approximate analytical method of two small parameters is performed. The steady statė motion of the system is determinded and the conditions of existance of multiple synchronization regimes are revealed.